dictyBase: a new Dictyostelium discoideum genome database - Kreppel, Lisa (Oxford University Press, 2004)
Dictyostelium discoideum is a powerful and genetically tractable model system used for the study of numerous cellular molecular mechanisms including chemotaxis, phagocytosis and signal transduction. The past 2 years have seen a significant expansion in the scope and accessibility of online resources for Dictyostelium. Recent advances have focused on the development of a new comprehensive online resource called dictyBase (http://dictybase.org). This database not only provides access to genomic data including functional annotation of genes, gene products and chromosomal mapping, but also to extensive biological information such as mutant phenotypes and corresponding reference material. In conjunction with additional sites (http://genome.imb-jena.de/dictyostelium/, http://dictyensembl.bioch.bcm.tmc.edu and http://www.sanger.ac.uk/Projects/D_discoideum/) from the genome sequencing and assembly centers, these improvements have expanded the scope of the Dictyostelium databases making them accessible and useful to any researcher interested in comparative and functional genomics in metazoan organisms.